1988
DOI: 10.1161/01.hyp.11.6.620
|View full text |Cite
|
Sign up to set email alerts
|

Vascular smooth muscle calponin. A novel troponin T-like protein.

Abstract: SUMMARY In a search for additional Ca 2+ regulatory components in vascular smooth muscle, a novel troponin T-like protein was purified from bovine aorta smooth muscle. The isolated protein was separated into several isoforms on isoelectric focusing. The major isoelectric variants were focused in the pH region of 8.4 to 9.1. The protein had slightly different molecular masses in the M r range of 35,000 on sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Its molar ratio relative to tropomyosin in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
2
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(110 citation statements)
references
References 40 publications
3
104
2
1
Order By: Relevance
“…The precise mechanism by which calponin negatively regulates BMP signalling remains to be elucidated. However, recent observations demonstrating physical and functional interactions between SMAD proteins and calmodulin (Zimmerman et al 1998) raise an interesting possibility that calponin, a calmodulin-binding protein (Takahashi et al 1986(Takahashi et al , 1988Wills et al 1993), might physically interact with SMAD proteins (Heldin et al 1997) or the calmodulin-SMAD complex and regulate the SMAD activity.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism by which calponin negatively regulates BMP signalling remains to be elucidated. However, recent observations demonstrating physical and functional interactions between SMAD proteins and calmodulin (Zimmerman et al 1998) raise an interesting possibility that calponin, a calmodulin-binding protein (Takahashi et al 1986(Takahashi et al , 1988Wills et al 1993), might physically interact with SMAD proteins (Heldin et al 1997) or the calmodulin-SMAD complex and regulate the SMAD activity.…”
Section: Discussionmentioning
confidence: 99%
“…Protein concentration was determined by the Lowry method based on molccular masses of 42 kOa for actin, 35 kDa for calponin [5] and 87 kDa for caldesmon [14]. ATPase activity was measured with an actomyosin made up of 0.5 mg/ml aorta actin and 0.125 mg/ml skeletal muscle myosin [15] in 50 or 90 mM KCI, l0 mM sodium azidc, 5 mM MgCb, I mM dithiothreitol.…”
Section: Asray Qf Proteismentioning
confidence: 99%
“…c~-actinin, filamin) and those which are associated with the contractile actomyosin domain, such as caldesmon [1,2]. Calponin is a recently discovered actin binding protein, present in all smooth muscle cells, which can also bind tropomyosin, Ca ~' +, and Ca=+.calmodulin [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Calponin is a family of actin thin filament-associated proteins, first identified in smooth muscle [1,2] and later found also in nonmuscle cells [3,4]. Biochemical studies showed that calponin binds to actin [1,5,6], Ca# + -calmodulin [1,2], S100 protein [7], caltropin (calcyclin) [8], tropomyosin [2,9], myosin [10,11] and desmin [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical studies showed that calponin binds to actin [1,5,6], Ca# + -calmodulin [1,2], S100 protein [7], caltropin (calcyclin) [8], tropomyosin [2,9], myosin [10,11] and desmin [12,13]. Calponin's interactions with contractile and cytoskeletal proteins have led to its proposed role in modulating the Ca# + signalling of contractile and cytoskeletal functions in smooth muscle and non-muscle cells.…”
Section: Introductionmentioning
confidence: 99%